Proceedings of the International Conference on Agents and Artificial Intelligence 2015
DOI: 10.5220/0005186203050316
|View full text |Cite
|
Sign up to set email alerts
|

Bioplausible Multiscale Filtering in Retinal to Cortical Processing as a Model of Computer Vision

Abstract: Visual illusions emerge as an attractive field of research with the discovery over the last century of a variety of deep and mysterious mechanisms of visual information processing in the human visual system. Among many classes of visual illusion relating to shape, brightness, colour and motion, "geometrical illusions" are essentially based on the misperception of orientation, size, and position. The main focus of this paper is on illusions of orientation, sometimes referred to as "tilt illusions", where parall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
3
2
1

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(34 citation statements)
references
References 49 publications
(82 reference statements)
1
33
0
Order By: Relevance
“…The patterns investigated have some similarities to Brightness/Lightness Illusions such as Irradiation [45,62], Simultaneous Brightness Contrast (SBC) [63][64][65] and White's effect [15,63,[65][66][67][68][69], but the difference between the explanation of these two subclasses of illusion is that for Tilt Illusions we seek for the prediction of tilt not the changes of Brightness/Lightness profile used to describe Brightness induction effects. The patterns under investigation seem to have mid-to high-level perceptual explanations, but in our previous investigations [14,[48][49][50] we have shown that the illusory tilt cues in these patterns are caused by multiscale retinal/cortical encoding by the simple cells and the Lateral Inhibition among them. We demonstrated how a low-level explanation of these patterns at multiple scales reveals the tilt cues in the local processing of the pattern, followed by higher levels of processing in the retina and the cortex for the integration of the local tilt cues for the final percept.…”
Section: The Focus Of Our Investigationmentioning
confidence: 80%
See 2 more Smart Citations
“…The patterns investigated have some similarities to Brightness/Lightness Illusions such as Irradiation [45,62], Simultaneous Brightness Contrast (SBC) [63][64][65] and White's effect [15,63,[65][66][67][68][69], but the difference between the explanation of these two subclasses of illusion is that for Tilt Illusions we seek for the prediction of tilt not the changes of Brightness/Lightness profile used to describe Brightness induction effects. The patterns under investigation seem to have mid-to high-level perceptual explanations, but in our previous investigations [14,[48][49][50] we have shown that the illusory tilt cues in these patterns are caused by multiscale retinal/cortical encoding by the simple cells and the Lateral Inhibition among them. We demonstrated how a low-level explanation of these patterns at multiple scales reveals the tilt cues in the local processing of the pattern, followed by higher levels of processing in the retina and the cortex for the integration of the local tilt cues for the final percept.…”
Section: The Focus Of Our Investigationmentioning
confidence: 80%
“…The patterns explored in this paper are 'second-order Tilt' Illusions [14] (Tile Illusions) involving the enhancement of contrast between textural elements of a background such as a checkerboard, for example Café Wall and Bulging checkerboard illusions. In the Café Wall illusion, the illusory tilt percept is the result of mortar lines between shifted rows of black and white tiles.…”
Section: History Of Geometrical Illusionsmentioning
confidence: 99%
See 1 more Smart Citation
“…A low-level filtering approach [17,19,22,23] have been explored here modelling the retinal/cortical simple cells in our early vision for revealing the tilt cues involved in the local and global perception of the Café Wall stimulus. The model has an embedded processing pipeline utilizing Hough transform to quantify the degrees of the inducing tilts appeared in the low-level representation for the stimulus in our model, referred to as the edge map at multiple scales.…”
Section: Resultsmentioning
confidence: 99%
“…The model here [17][18][19][20][21][22] is a most primitive implementation for the contrast sensitivity of RGCs based on classical circular center and surround organization of the retinal RFs [33,34]. The output of the model is a simulated result for the responses of the retinal/cortical simple cells to a stimuli/image.…”
Section: Introductionmentioning
confidence: 99%